Revision of the Indo-Pacific species of the genus Leucosyrinx Dall, 1889 (Neogastropoda: Conoidea: Pseudomelatomidae) - Yuri I. Kantor; Alexander Fedosov; Nicolas Puillandre (European Journal of Taxonomy)
The genus Leucosyrinx Dall, 1889 is one of the highly diverse genera of the family Pseudomelatomidae, distributed across the Atlantic and Pacific Oceans. It remains poorly defined based on conchological characters. The last revision of the genus was published by Powell (1969; Indo-Pacific Mollusca 2 (10): 207–415), in which many species were erroneously included, while others belonging to Leucosyrinx were attributed to different genera. For the first time, we have revised the Indo-Pacific species of the genus within the framework of integrative taxonomy, utilizing molecular-grade material accumulated in the Muséum national d’Histoire naturelle, France. Molecular phylogenetic analysis revealed the existence of 62 secondary species hypotheses (SSHs) in our material, with 12 of them corresponding to already named species. The remaining 50 SSHs represent new species, of which 24 are described here, while 26 remain unnamed due to insufficient material. We refined the morphological characteristics of Leucosyrinx based on shell analysis of sequenced species from the genus, as well as from similar genera, particularly Comitas, Sibogasyrinx, and Comispira (the latter two belonging to Cochlespiridae). This allowed us to assign 18 previously named species to Leucosyrinx, and conditionally attribute four more, bringing the total number of species in the Indo-Pacific to 84, of which 58 are named. Numerous cases of cryptic species, which are nearly indistinguishable morphologically, were recorded within Leucosyrinx. The genus is confined to the upper bathyal zone, ranging from 195 to 1634 m in depth, with most occurrences between 500 and 1000 m. The highest species richness (30 species) was recorded in Papua New Guinea and the Solomon Islands, though this is likely due to more intensive sampling of the upper bathyal zone in these regions compared to other areas of the Indo-Pacific.